In the garden - Schwartz, David M.; Kuhn, Dwight (Milwaukee, Wis. : Gareth Stevens Pub., 1999)
Explores the peas, potatoes, pumpkins, and other vegetables in a garden, as well as the insects and other animals that help them grow.
Includes bibliographical references (p. 23) and index.
73788
Keywords: Garden ecology -- Juvenile literature; Vegetables; Gardens; Garden animals; Garden ecology; Ecology